Implikasi Ideologi Pancasila pada Gerakan Sosial Islam dalam Prinsip Demokrasi Konstitusional - Tatu Afifah; Fuqoha Fuqoha; Sukendar Sukendar (Ajudikasi : Jurnal Ilmu Hukum, 2020)
Pancasila implementation should not be used as a substantive source in aspects of law and legislation in Indonesia. Pancasila as the highest source of law in Indonesia is actualized in every behavior and action both individually and collectively. Social movements are a characteristic and manifestation of democratic principles as a reflection and reaction to social dynamics in society. The research method used is in the form of qualitative research which tries to explore a meaning arising from social dynamics. The influence of the Pancasila ideology on every social movement, especially the Islamic social movement, is based on the view of life together within the framework of the Indonesian nation and the concept of a rule of law. The consequence of the principle of constitutional democracy in implementing the Pancasila values ​​framework is not a threat to democracy, because the values ​​of Pancasila also provide respect for the rights of the people which are in line with the principles of constitutional democracy. Keywords: Implication; Ideology; Pancasila; Social movement; Constitutional.